Assessment of arch width changes in Class I and Class II Division 1 patients treated with fixed orthodontics - Parajuli, Umesh; Bajracharya, Manish; Pandey, Manju; Gurung, Ima; Tuladhar, Sapna Laxmi (Journal of Gandaki Medical College-Nepal, 2021)
Background: The orthodontic treatment should aim to maintain the inter-canine and inter-molar width to that of the pre-treatment values. The study was conducted with objective to evaluate arch width changes in Class I and Class II patients treated with fixed orthodontics.Methods: This was a hospital-based cross-sectional study with two study groups. The first group included patients with Class I malocclusion, treated with four first premolar extractions and the second group included patients with Class II Div 1 malocclusion, treated with upper two first premolar extractions. The inter-canine and inter-molar width of the pre and post-treatment study model were measured. To compare the changes observed amongst two groups, independent samples t-test was performed. A paired sample t-test was used to evaluate the treatment changes within each group.Results: There was significant increase in inter-canine width in both maxillary and mandibular arches in both the groups. In Class I extraction group there was significant decrease in the inter-molar width in both maxillary and mandibular arches. The Class II Div1 maxillary extraction group also showed significant increase in inter-canine width in both maxillary and mandibular arches. In the same group there was decrease in post treatmentMethods: This was a hospital-based cross-sectional study with two study groups. The first group included patients with Class I malocclusion, treated with four first premolar extractions and the second group included patients with Class II Div 1 malocclusion, treated with upper two first premolar extractions. The inter-canine and inter-molar width of the pre and post-treatment study model were measured. To compare the changes observed amongst two groups, independent samples t-test was performed.  A paired sample t-test was used to evaluate the treatment changes within each group.Results: There was significant increase in inter-canine width in both maxillary and mandibular arches in both the groups. In Class I extraction group there was significant decrease in the inter-molar width in both maxillary and mandibular arches. The Class II Div1 maxillary extraction group also showed significant increase in inter-canine width in both maxillary and mandibular arches. In the same group there was decrease in post-treatment inter-molar width in both arches with significant decrease in the maxillary inter-molar width.Conclusion: There was increase in inter-canine width in both Class I extraction group and Class II Div 1 maxillary extraction group with decrease in inter-molar width in both the groups.